Comprehensive evaluation of the Ruoergai Prairie ecosystem upstream of the Yellow River - Xu, Xiangning; Yang, Qingwen; Xiang, Guoping; Liu, Tao; Yang, Mengjie; Xiong, Xi; Jiang, Tao (Frontiers in Ecology and Evolution, 2023)
With complex and diverse ecosystem types and complete ecological elements such as mountains, rivers, forests, farmlands, lakes, grasslands, sand, and glaciers, the Ruoergai Prairie upstream of the Yellow River is an integral part of the Qinghai-Tibet Ecological barrier and a critical area for ensuring the ecological security of China. In the Ruoergai Prairie, climate change and human activities have led to grassland degradation, water and soil loss, and a shrinking forest area, which has highlighted the need for ecological restoration. Therefore, a comprehensive ecosystem evaluation is of great significance for ecosystem restoration. This study evaluated the ecosystem quality, ecosystem service function importance, ecological vulnerability, ecological protection importance, ecological resilience, and ecological landscape patterns of prairies, wetlands, and forests. The ecosystem quality of the study area was medium to good. The ecosystem service function of the study area with weak ecosystem resilience is important. However, the ecological landscape in the study area has been heavily degraded. Therefore, the protection and restoration of mountains, waters, forests, farmlands, lakes, grasslands, sand, and glaciers are needed.